(untitled) (Heritage, 2025)
This paper analyzes Serbia’s participation in the Oriental Pavilion of the 1885. Budapest National Exhibition, a major cultural and economic event within the Austro-Hungarian Monarchy. While conceived as a Hungarian national showcase, the Exhibition included a designated space for Balkan and Eastern countries, with the Oriental Pavilion serving as both a symbolic and practical venue for regional interaction. Serbia’s section was among the most prominent, structured as a scenographic narrative of domestic production, cultural identity, and economic potential. The presentation included handicrafts, agricultural products, industrial items, and museum-quality artifacts, accompanied by wax figures, traditional costumes, and artworks, including contributions from Queen Natalija. The scenography and open display concept offered a contrast to the more static, museum-like displays of other Eastern sections, resulting in strong public appeal and positive media coverage. Contemporary press described the Serbian display as disciplined, well-organized, and elegant, and official reports emphasized its alignment with Serbia’s economic realities and aspirations. The participation was not merely representational but carried significant diplomatic and economic implications. Visits from the Habsburg imperial family, as well as the Serbian royal couple and several state and professional delegations, underlined the political relevance of the Pavilion. Hungary’s goal of expanding trade eastward was reflected in both the structure and reception of the Serbian section, which successfully projected the image of a dynamic, modernizing Balkan state. As noted in the press: if the Exhibition was the ornament of the Hungarian nation, then the Oriental Pavilion could rightly be called the ornament of the Budapest Exhibition.